A large filarial hydrocele in Kenya: a case report - Waihenya, Charles; Githui, Sheila; Schouame, Edgard (Frontiers in Tropical Diseases, 2024)
Morbidity Management and Disability Prevention (MMDP) remains a key aspect of the Global project for the Elimination of Lymphatic Filariasis (GPELF) a program launched by WHO in the year 2000. In line with this mandate the Ministry of Health in Kenya having already achieved 95% Mass Drug Administration (MDA) by use of door-to-door drug administration (DA-albendazole and diethylcarbamazine) yearly for 5 years. The dosages used were albendazole 400mg and diethylcarbamazine citrate 6mg/Kg orally. Three drug combination by adding ivermectin (150ug/Kg) have been used in areas where the success of DA was suboptimal following the recommendation by WHO to speed up the elimination of lymphatic filariasis and areas endemic with onchocerciasis. A training workshop for surgeons and medical officers was organized in May 2023 for the surgical management of lymphatic hydroceles in the Coastal region of Kenya which is an endemic area for lymphatic filariasis. During the index training workshop in Kilifi, we encountered and managed an 83-year-old male who lived with a large grade 4 hydrocele and a right inguinal hernia for over six decades. We share our experience with this case report in this manuscript (large bilateral filarial hydrocele and right inguinal hernia for a period of sixty years. The objective of writing this report is to share our experience and the progress of MMDP program in Kenya.